Effects of chains squat training with different chain load ratio on the explosive strength of young basketball players` lower limbs - Jiang, D.; Xu, G. (Frontiers in Physiology, 2022)
The purpose of this study was to explore the effects of the chain squat training (CST) with different chain load ratio (0, 10%, 20% and 30%) on the explosive power of the lower limbs of adolescent male basketball players. Forty-four youth basketball players (age 15.48 ± 0.81years, body mass 78.86 ± 12.04kg, height 184.95 ± 6.71cm) were randomly allocated to one of the four groups: traditional squat training (TST), 10% chains squat training (10% CST), 20% chains squat training (20% CST), and 30% chains squat training (30% CST). Training interventions were performed 2 times per week for 6weeks, and at the week before (Pre) and after (Post) the 6-week CST program with different chain load ratio, the no-step vertical jump, standing long jump, 15m shuttle run, 1 RM squat and 30m sprint test were performed. A 4 (group) × 2 (time) repeated measures analysis of variances (ANOVA) was calculated to show the scatter of each variable, and the Bonferroni`s post-hoc test was used for multiple comparisons, in addition the partial eta-squared (?2) was calculated as an estimate of the ES. Significant time × group interaction was noticed for the no-step vertical jump (p < 0.001; ?2 = 0.611), standing long jump (p < 0.001; ?2 = 0.490) and 1 RM squat (p < 0.01; ?2 = 0.333) indicating that better improvements appear in CST compared to TST. However, significant time × group interaction was noted for 15m shuttle run (p < 0.001; ?2 = 0.428), in favor of TST compared to CST. In addition, the improvements in 30m sprint were similar between all groups. In conclusion, CST with more chain load has better training effects on lower limb explosive strength and maximum strength, based on the improvement in 1RM squat and jumping performance. Besides, compared with TST, CST with more chain load might not help to develop better velocity adaptation at higher range of movement.